Conceptual physics - Hewitt, Paul G., 1931- (Boston : Pearson Education, 2014)
Since defining this course 30 years ago, Paul Hewitt's best-selling text continues as the benchmark by which all others are judged. In Conceptual Physics Twelfth Edition Paul Hewitt makes physics interesting, understandable, and relevant for non-science majors. The Twelfth Edition will delight students with informative and fun Hewitt-Drew-It screencasts, updated content and applications. Hewitt's text is guided by the principle of "concepts before calculations" and is famous for engaging students with analogies and imagery from the real-world that build a strong conceptual understanding of physical principles ranging from classical mechanics to modern physics. This program presents a better teaching and learning experience–for you and your students. •Prepare for lecture: NEW! 100 Hewitt-Drew-It screencasts, authored and narrated by Paul Hewitt, explain physics concepts through animation and narration. The exciting new Screencasts, accessed through QR codes in the textbook, will enable students to engage with the physics concepts more actively outside of class. •Make physics delightful: Relevant and accessible narrative, analogies from real-world situations, and simple representations of the underlying mathematical relationships make physics more appealing to students. •Build a strong conceptual understanding of physics: Students gain a solid understanding of physics through practice and problem solving in the book.
1. About Science I. MECHANICS 2. Newton's First Law of Motion: Inertia 3. Linear Motion 4. Newton's Second Law of Motion: Force and Acceleration 5. Newton's Third Law of Motion: Action and Reaction 6. Momentum 7. Energy 8. Rotational Motion 9. Gravity 10. Projectile and Satellite Motion II. PROPERTIES OF MATTER 11. Atomic Nature of Matter 12. Solids 13. Liquids 14. Gases and Plasmas III. HEAT 15. Temperature, Heat and Expansion 16. Heat Transfer 17. Change of Phase 18. Thermodynamics IV. SOUND 19. Vibrations and Waves 20. Sound 21. Musical Sounds V. ELECTRICITY AND MAGNETISM 22. Electrostatics 23. Electric Current 24. Magnetism 25. Electromagnetic Induction VI. LIGHT 26. Properties of Light 27. Color 28. Reflection and Refraction 29. Light Waves 30. Light Emission 31. Light Quanta VII. ATOMIC AND NUCLEAR PHYSICS 32. The Atom and the Quantum 33. Atomic Nucleus and Radioactivity 34. Nuclear Fission and Fusion VIII. RELATIVITY 35. Special Theory of Relativity 36. General Theory of Relativity Appendices A. Systems of Measurement B. More About Motion C. Graphing D. More About Vectors E. Exponential Growth and Doubling Time
Global edition